2007
DOI: 10.4269/ajtmh.2007.77.411
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intermittent Preventive Anti-Malarial Treatment on the Growth and Nutritional Status of Preschool Children in Rural Senegal (West Africa)

Abstract: Negative consequences of malaria might account for seasonality in nutritional status in children in the Sahel. We report the impact of a randomized, double-blind, placebo-controlled trial of seasonal intermittent preventive anti-malarial treatment on growth and nutritional status in 1,063 Senegalese preschool children. A combination of artesunate and sulfadoxine-pyrimethamine was given monthly from September to November. In the intervention arm, mean weight gain was significantly greater (122.9 ± 340 versus 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
4
15
0
Order By: Relevance
“…We did not detect any difference between the intervention and control arms in wasting, stunting, or under weight. This finding is consistent with a previous study in Senegal [25], which did not find evidence of an impact of IPTc on wasting, stunting, or being under weight at the end of the transmission season but only on triceps and subscapular skinfold, indicators that were not assessed in our study. However, in line with the Senegalese study, we found an increase in weight gain in the IPTc arm compared to the control arm during the course of the intervention period.…”
Section: Discussionsupporting
confidence: 94%
“…We did not detect any difference between the intervention and control arms in wasting, stunting, or under weight. This finding is consistent with a previous study in Senegal [25], which did not find evidence of an impact of IPTc on wasting, stunting, or being under weight at the end of the transmission season but only on triceps and subscapular skinfold, indicators that were not assessed in our study. However, in line with the Senegalese study, we found an increase in weight gain in the IPTc arm compared to the control arm during the course of the intervention period.…”
Section: Discussionsupporting
confidence: 94%
“…Administration of a total of 1700 doses of SP to 546 children (on an average of 3.1 occasions per child) prevented 101 episodes of malaria during an average period of follow up of 2.7 months, a saving of 1 clinical episode of malaria for every 17 doses of SP given, a figure comparable to that seen in studies of IPTi. The reduction in the number of clinical episodes of malaria was associated with a 27% reduction in the overall number of clinic visits during the follow-up period and children who received SP were better nourished than those who received placebo, consistent with findings in other studies of IPT in children [29]. Deaths and hospital admissions were fewer in children who received SP than in those who received placebo but numbers of events are too small for conclusions to be drawn.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, we sought to determine whether malaria morbidity management might be an explanation for the impressive 42% decrease in prevalence of stunting (from 28.3 to 16.3%) observed in both placebo and malaria-preventively treated children at the end of the 2002-2003 IPT study (11). Indeed, all children included in this study benefited from weekly active malaria case detection by home visits and prompt treatment.…”
Section: Discussionmentioning
confidence: 94%
“…The intervention was highly successful; the risk of a clinical attack was reduced by 86% (10). The prevalence of wasting increased significantly in the control group during the transmission season but remained constant in intervention children (11). In addition, an unexpected 42% decrease in stunting was observed in both groups during follow-up: from 28.3% (95% CI: 25.6-31.0) at inclusion to 16.3% (95% CI: 13.9-18.7) 15 mo later at the end of the intervention (P , 0.0001).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation